Implementation of Learning Centers in Critical Thinking Skills in Kindergarten Children Harapan Bangsa Jeranglah Tinggi - Dina Maryana; Dwi Putri Maranatha; Puti Yusnita; Onek Purnama; Yelmi Susanti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study examines the implementation of center-based learning to develop critical thinking skills in children aged 4–6 years at TK Harapan Bangsa Jeranglah Tinggi. Employing a descriptive qualitative design, the research involved 16 children and two teachers over six weeks, utilizing systematic observation, assessment rubrics, field notes, and interviews. Data were analyzed thematically and descriptively. Results demonstrate consistent improvement across four indicators: questioning, comparing, problem-solving, and reflective reasoning, with an average score increase of 64.9%. Teacher facilitation strategies, particularly open-ended questioning, cognitive modeling, and responsive scaffolding, emerged as primary success drivers. Spatial constraints and transition challenges were effectively addressed through weekly theme rotation and structured visual schedules. The study concludes that child-centered center-based learning successfully establishes a meaningful play environment that cultivates early inquiry habits and foundational reasoning. These findings recommend strengthening preschool educators’ facilitation competencies and providing open-ended materials to sustain cognitive development.